Dampak Paparan Konten Digital Ultra-Cepat Terhadap Regulasi Emosi Dan Fungsi Eksekutif Remaja - Mutia Mawardah; Tiara Khairunisa (Jurnal Bina Ilmu Cendekia, 2025)
The rapid development of digital technology has increased adolescents’ exposure to ultra-fast digital content, such as short-form videos on social media platforms. This study aims to examine the impact of exposure to ultra-fast digital content on emotion regulation and executive functions among adolescents. Using a positivistic quantitative approach with a descriptive-correlational design, data were collected from 36 adolescent respondents through questionnaires employing a five-point Likert scale, supported by interviews and observations. The results indicate that the level of exposure to ultra-fast digital content among adolescents is in the moderate to high category. Emotion regulation and executive functions are generally at a moderate level, with notable difficulties in attention control and impulse control. Statistical analysis reveals that higher exposure to ultra-fast digital content is associated with lower levels of emotion regulation and executive functions. These findings suggest that ultra-fast digital content may affect adolescents’ emotional and cognitive control processes, particularly during a critical developmental period. The study highlights the importance of digital literacy and balanced media use to support healthy emotional and cognitive development among adolescents.